A Study on Family perception and Quality perception of Women Executives in Chennai City - Sakthivel Murugan, M.; Sujatha, T. (International Journal of Psychosocial Rehabilitation, 2024)
Women is always have positive thinking and action to achieve better work role in the organization. Women always work towards achieving their career plan well and implement in time. The various research studies focuson relevance of women executives globally the perception of women towards work is positive and assertive nature. There is a significant upliftment and achievement of women work force in various sections in the corporate social and other fields. In this context, the present study is attempted in Family perception and Quality perception of women Executives in Chennai city which may lead to business performance.